Pre-treatment for reducing the physico-chemical parameters of leached generation in sanitary land (Research, Society and Development, 2021)
The objective of this work was to evaluate the pilot-scale filtration process in the pre-treatment of landfill leachate through physical-chemical analyzes. Four types of filters were evaluated; in which the filtering materials used were sand, medium and coarse sand, activated carbon, clay, gravel n ° 0 and gravel n ° 1. Statistical analysis was performed by analysis of variance (ANOVA) followed by the Tukey test, when applicable. Data were expressed as mean ± standard deviation and P values ​​